(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2012)
As part of the Maharashtra Emergency EarthquakeRehabilitation Programme (MEERP), one of the mandated activities of theGovernment of Maharashtra is the preparation of a comprehensive multi-hazardDisaster Management Plan for the state of Maharashtra. The World Bank, UNDP andDFID (Department for International Development, UK, formerly ODA) aresupporting different complementary components of this multi-faceted effort. Itis an ambitious programme, with emphasis on disaster management response,disaster awareness and education. It has a State plan as the core and all thedistrict plans of Maharashtra forming the superstructure. These disastermanagement plans identify administrative and technical measures essential todisaster preparedness, response action, and mitigation efforts. These planshave crystallised an implementation programme comprising a number of componentswhich are detailed later in the section.